Unlocking Synergistic Photo-Fenton Catalysis with Magnetic SrFe12O19/g-C3N4 Heterojunction for Sustainable Oxytetracycline Degradation: Mechanisms and Applications - Song Cui; Yaocong Liu; Xiaolong Dong; Xiaohu Fan (Nanomaterials)
The widespread contamination of aquatic environments by tetracycline antibiotics (TCs) poses a substantial threat to public health and ecosystem stability. Although photo-Fenton processes have demonstrated remarkable efficacy in degrading TCs, their practical application is limited by challenges associated with catalyst recyclability. This study reports the development of a novel magnetic recoverable SrFe12O19/g-C3N4 heterostructure photocatalyst synthesized via a facile one-step co-calcination method using industrial-grade precursors. Comprehensive characterization revealed that nitrogen defects and the formation of heterojunction structures significantly suppress electron (e−)–hole (h+) pair recombination, thereby markedly enhancing catalytic activity. The optimized 7-SFO/CN composite removes over 90% of oxytetracycline (OTC) within 60 min, achieving degradation rate constants of 0.0393 min−1, which are 9.1 times higher than those of SrFe12O19 (0.0043 min−1) and 4.2 times higher than those of g-C3N4 (0.0094 min−1). The effectively separated e− play three critical roles: (i) directly activating H2O2 to generate ·OH radicals, (ii) promoting the redox cycling of Fe2+/Fe3+ ions, and (iii) reducing dissolved oxygen to form ·O2− species. Concurrently, h+ directly oxidize OTC molecules through surface-mediated reactions. Furthermore, the 7-SFO/CN composite exhibits exceptional operational stability and applicability, offering a transformative approach for scalable photocatalytic water treatment systems. This work provides an effective strategy for designing efficient and recoverable photocatalysts for environmental remediation.